Cover Picture: A Practical Approach for the Oxidation of Unactivated Csp3H Bonds with o‐Nitro(diacetoxyiodo)benzene as an Efficient Hypervalent Iodine(III)‐Based Oxidizing Agent (Asian J. Org. Chem. 9/2014). Issue 9 (September 2014) - Moteki, Shin A.; Selvakumar, Sermadurai; Zhang, Tiexin; Usui, Asuka; Maruoka, Keiji
<x xml:space="preserve">Abstract</x> The practical, site‐selective oxidation of unactivated Csp3‐H bonds was achieved by the use of a stable ortho‐nitrophenyl‐substituted hypervalent iodine(III) reagent. In their Communication on page 932 ff., Keiji Maruoka and co‐workers show that the presence of the nitro group adjacent to the iodine center leads to a single substitution of an acetate ligand by tert‐butyl hydroperoxide. Hence, the generation of a strong iodanyl radical was achieved, which can activate inert Csp3‐H bonds in a highly efficient manner. Also, the use of such a bulky reagent "tips the balance" in favor of oxidation at the C3 over the C4 position on substituted cyclohexane rings. Image credit: Asuka Usui.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>